Nudging effects on consumer preferences and willingness to pay for lycopene-enriched fresh tomatoes - Maria De Salvo; Isabella Trovato; Laura Giuffrida; Marika Cerro; Giovanni Signorello; Giuseppe Cucuzza (Future Foods, 2025)
Using a Discrete Choice Experiment, this study examines how informational prompts about the nutraceutical properties of tomatoes influence consumers’ perceptions and preferences for lycopene-enriched fresh tomatoes. The results show that such nudges effectively increase consumer interest in functional foods by raising the perceived importance of their health-related benefits. Furthermore, nudging significantly impacts Willingness To Pay (WTP), with consumers exhibiting higher WTP for tomatoes with enhanced nutraceutical attributes when exposed to the informational prompts. These findings offer valuable insights for promoting healthier dietary choices and for guiding the development of food products that align with shifting consumer values and health consciousness.